2022
DOI: 10.1055/a-1877-0421
|View full text |Cite
|
Sign up to set email alerts
|

Hyperacute in-Stent Thrombosis Causing Large Vessel Occlusion after Stent-Assisted Aneurysm Coiling Secondary to Complete Clopidogrel and Prasugrel Resistance: a Case Report

Abstract: Dual anti-platelet therapy (DAPT) is standard treatment for endoluminal stent insertion, and complete resistance to DAPT is rare. A case of in-stent thrombosis occurring three hours after stent-assisted coiling of ICA aneurysm is presented despite compliance with DAPT. Platelet function tests (PFT) revealed complete clopidogrel and prasugrel resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…A recent study demonstrated the efficacy of thromboelastography-platelet mapping in stent-assisted coiling for ruptured aneurysms, which would allow for an individualized antiplatelet regimen [ 57 ]. This would help prevent thromboembolic complications from occurring in those with antiplatelet resistance [ 58 ]. The choice for DAPT in SAC should consider the patient’s risk of bleeding, history of noncompliance, and individual drug metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study demonstrated the efficacy of thromboelastography-platelet mapping in stent-assisted coiling for ruptured aneurysms, which would allow for an individualized antiplatelet regimen [ 57 ]. This would help prevent thromboembolic complications from occurring in those with antiplatelet resistance [ 58 ]. The choice for DAPT in SAC should consider the patient’s risk of bleeding, history of noncompliance, and individual drug metabolism.…”
Section: Discussionmentioning
confidence: 99%